2013
DOI: 10.2169/internalmedicine.52.8617
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Patients with Parkinson's Disease

Abstract: Objective To investigate the prevalence and clinical correlates of anxiety and depression in patients with Parkinson's disease (PD) and to examine the relationship between anxiety and depression and the quality of life (QOL). Methods One hundred and seventeen patients with PD completed the State-Trait Anxiety Inventory (STAI), the Beck Depression Inventory Second Edition (BDI-II), Starkstein's Apathy Scale (AS) and QOL battery. Hoehn and Yahr (HY) staging, the Unified Parkinson's Disease Rating Scale (UPDRS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
80
6
17

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 34 publications
13
80
6
17
Order By: Relevance
“…5 Depression is one of the major health problems in patients with PD. 6,7,38,39 Although, PD primarily is a movement disorder, depression in PD is difficult task and the predictors are complex and debatable. 8,38 The true prevalence of depression in PD is difficult to determine because there are no standardized assessment tools designed to evaluate depressive symptoms in the context of this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Depression is one of the major health problems in patients with PD. 6,7,38,39 Although, PD primarily is a movement disorder, depression in PD is difficult task and the predictors are complex and debatable. 8,38 The true prevalence of depression in PD is difficult to determine because there are no standardized assessment tools designed to evaluate depressive symptoms in the context of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31] Whereas a recent study reported that PD patients with depression were associated with different demographic and clinical factors. [38][39][40][41] These findings emphasize the need to study the factors associated with depression in this population. It is well studied in western population but data from Asia especially sub-continent is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that depression and anxiety negatively impact selfreport of quality of life in PD, [5][6][7][8][9][10][11] more so than motor symptom severity. 7,9 One study found that depression has more than twice the impact of motor symptoms on overall health status in PD.…”
Section: Impactmentioning
confidence: 99%
“…7,9 One study found that depression has more than twice the impact of motor symptoms on overall health status in PD. 12 Many studies report comparable effects of depression and anxiety on quality of life, but at least one suggested that anxiety may be the strongest predictor of quality of life in PD.…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation